SOCIALIZATION OF GAYO BUFFALO CHARACTERISTICS BASED ON NATIONAL STANDARD (SNI) NUMBER 8292-6:2023 IN LINGE DISTRICT, CENTRAL ACEH REGENCY - Sofia, Aiya; Al Adam, Koji; Fatmala, Nanda (LPPM Universitas Al Muslim, 2024)
Buffalo is a large ruminant animal that can be used as a producer of meat, milk and work. Apart from that, buffalo also have a high carcass percentage. Gayo buffalo are a local livestock resource, whose maintenance is carried out using an extensive system or is released into livestock. This community service activity aimed to increase the knowledge and skills of breeders in raising Gayo Buffalo to produce Gayo Buffalo with superior characteristics in accordance with National Standard No.8292-6:2023. The method for implementing this activity included observation and socialization regarding the characteristics of Gayo Buffalo livestock. Community service activities were carried out in Pantan Nangka Village, Linge District, Central Aceh Regency, which were attended by local breeders. The results of the activities showed that all participants in the farmer group were able to properly understand and recognize the characteristics of Gayo buffalo and gain knowledge related to good buffalo breeding management.